Strategi Pengelolaan Perikanan Udang Pasca Moratorium Perikanan Di Provinsi Papua Barat - Zulkifli Henan; Selvi Tebay; Roni Bawole; Ridwan Sala; Paulus Boli; Gandi Y.S. Purba (Jurnal Sumberdaya Akuatik Indopasifik, 2021)
The implementation of the fisheries moratorium has an impact on the shrimp industry, namely the cessation of shrimp fishing operations and termination of employees of some shrimp companies in the West Papua Province. The aim of this research is develop a shrimp fisheries management strategy at West papua Province after the end of the moratorium on fisheries so that the shrimp industry can contribute to job creation and increase local revenue. SWOT analysis is used to identify internal and external factors as the basis for the shrimp fisheries policy direction. Recommended strategies for managing Shrimp fisheries; 1) Increasing awareness of coastal communities towards environmental sustainability. 2) Optimizing the productivity of small-scale capture fisheries through improving the quality of fishermen's human resources. 3) Strict law enforcement and improvement of community based fish resource utilization monitoring systems, including improving the quality of HR supervisors. 4) Development of capture fisheries infrastructure, including fuel supply logistics systems. 5) Increased cooperation in fishing business through partnership programs, to ensure the sustainability of operational costs, and the development of business investment. 6) Development of value-added capture fisheries for the welfare of fishermen's income.